2017
DOI: 10.1590/1806-9061-2016-0413
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Probiotic Potential of Lactobacillus Salivarius and Pediococcus Pentosaceus in Specific Pathogen Free Chickens

Abstract: This study was conducted to isolate Lactobacillus salivarius and Pediococcus pentosaceus strains from cecal content and investigate their probiotic potential in specific pathogen free (SPF) chickens. L. salivarius and P. pentosaceus strains were isolated from the cecal content of SPF chickens and identified by 16s rDNA sequence analysis by BLAST analysis at the National Center for Biotechnology Information and phylogenetic analysis using DNAStar software. In an in vivo experiment, 180 7-day-old SPF chickens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…P. pentosaceus may also exhibit inhibitory activity toward other P. pentosaceus strains differing in antimicrobial production as well as toward P. acidilactici and Lactobacillus plantarum, which may share niches with P. pentosaceus (Luc de Vuyst, 1994). In addition to its antibacterial ability, other functions of P. pentosaceus have also attracted much attention, such as regulating immunity (Silva et al, 2017;Bamba et al, 2018), and improving the growth and final meat quality as well as gut micro-environment of chicken and fish (Dawood et al, 2016;Adel et al, 2017;Chen et al, 2017). Recently, some strains were reported to alleviate toxicity from vital organs such as liver and intestine caused by cadmium (Cd) exposure in a murine model (Dubey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…P. pentosaceus may also exhibit inhibitory activity toward other P. pentosaceus strains differing in antimicrobial production as well as toward P. acidilactici and Lactobacillus plantarum, which may share niches with P. pentosaceus (Luc de Vuyst, 1994). In addition to its antibacterial ability, other functions of P. pentosaceus have also attracted much attention, such as regulating immunity (Silva et al, 2017;Bamba et al, 2018), and improving the growth and final meat quality as well as gut micro-environment of chicken and fish (Dawood et al, 2016;Adel et al, 2017;Chen et al, 2017). Recently, some strains were reported to alleviate toxicity from vital organs such as liver and intestine caused by cadmium (Cd) exposure in a murine model (Dubey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hill et al ( 2014 ), probiotics are defined as live microorganisms that when consumed in adequate amounts exert beneficial effects in the host with a GRAS status (Generally Regarded As Safe). Probiotic strains mainly include members of the genera Lactobacillus and Bifidobacterium , but bacteria belonging to the genus Pedioccocus have also been tested and already used (Vidhyasagar and Jeevaratnam, 2012 ; Martino et al, 2013 ; Belhadj et al, 2014 ; Savedboworn et al, 2014 ; Dubey et al, 2015 ; Chen et al, 2017 ). Such investigations have led to an obvious support of the significance of Pediococci in the field of probiotics, indicating that new isolated strains from various food matrices and belonging to this genus may play a key role to be used in new generation of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained in this study revealed that the oral administration of L. salivarius expressing 3D8 scFv increased the body weight gain during the overall experimental period. Previous studies, such as those conducted by Chen, Zhu, and Qiu (2017) and Shokryazdan et al (2017), revealed that L. salivarius administered as feed significantly increases the body weight gain of chickens. Balamuralikrishnan, Lee, and Kim (2017) suggested that L. salivarius could increase the body weight gain without affecting the feed intake or feed conversation ratio during the overall experimental period.…”
Section: Discussionmentioning
confidence: 91%